From Image to Impact: The Viral Spread of “All Eyes on Rafah” and Its Global Repercussions - Teguh Luhuringbudi; Purnama Putra; Fitri Liza; Mowafg Abrahem Masuwd; Dewi Nita Utami; Abdulnasir Dhaw Alsayd (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
The viral dissemination of the AI-generated image “All Eyes on Rafah” has had a profound global impact, igniting widespread humanitarian concern and political discourse. This study employs a qualitative-descriptive interdisciplinary approach, drawing on Agenda Setting Theory (McCombs & Shaw), Marshall McLuhan’s media theory, and Alexander Wendt’s Constructivism to analyze this phenomenon. Primary data comprise viral news reports and social media images documenting the Israeli bombing of Rafah refugee camps, which resulted in approximately 55 civilian casualties. Data collection involved comprehensive reading, detailed note-taking, and thematic categorization, followed by analytical stages of restatement, description, and interpretation. The findings underscore the pivotal role of AI and social media in amplifying humanitarian crises, demonstrating how media agendas shape public perception and influence international political responses. This research advances the understanding of the interplay between digital media, political communication, and human rights advocacy, highlighting both the transformative potential and ethical complexities of AI-generated imagery in mobilizing global attention and action.